Colorado Potato Beetle, Leptinotarsa decemlineata (Say) and False Potato Beetle, Leptinotarsa juncta (Germar) (Insecta: Coleoptera: Chrysomelidae) - Richard L. Jacques, Jr.; Thomas R. Fasulo (EDIS, 2009)
Revised! EENY146, a 6-page illustrated fact sheet by Richard L. Jacques, Jr. and Thomas R. Fasulo, is part of the Featured Creatures collection. It describes these two species of potato beetles that are found in the eastern states — distribution, description, life cycle, hosts, Key to the Leptinotarsa spp. of Florida, and management. Includes references. Published by the UF Department of Entomology and Nematology, October 2009.